Soy sauce and its umami taste: a link from the past to current situation. - Lioe, Hanifah Nuryani; Selamat, Jinap; Yasuda, Masaaki (2010)
Soy sauce taste has become a focus of umami taste research. Umami taste is a 5th basic taste, which is associated to a palatable and pleasurable taste of food. Soy sauce has been used as an umami seasoning since the ancient time in Asia. The complex fermentation process occurred to soy beans, as the raw material in the soy sauce production, gives a distinct delicious taste. The recent investigation on Japanese and Indonesian soy sauces revealed that this taste is primarily due to umami components which have molecular weights lower than 500 Da. Free amino acids are the low molecular compounds that have an important role to the taste, in the presence of sodium salt. The intense umami taste found in the soy sauces may also be a result from the interaction between umami components and other tastants. Small peptides are also present, but have very low, almost undetected umami taste intensities investigated in their fractions.